2019
DOI: 10.3847/1538-4365/ab0825
|View full text |Cite
|
Sign up to set email alerts
|

The Period–Luminosity Relations of Red Supergiants in M33 and M31

Abstract: Based on previously selected preliminary samples of Red Supergiants (RSGs) in M33 and M31, the foreground stars and luminous Asymptotic Giant Branch stars (AGBs) are further excluded, which leads to the samples of 717 RSGs in M33 and 420 RSGs in M31.With the time-series data from the iPTF survey spanning nearly 2000 days, the period and amplitude of RSGs are analyzed. According to the lightcurves characteristics, they are classified into four categories in which 84 and 56 objects in M33 and M31 respectively ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 68 publications
4
47
0
Order By: Relevance
“…It is clear that pulsations following a P-L relation are present in most RSGs in the Local Group and that this relation does not depend on the metallicity (Ren et al 2019). In order to consider RSGs "standard candles" (as suggested by Glass 1979), factors like the abundance of irregular variables, mass loss, dust production and the additional sources of long-period variability need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that pulsations following a P-L relation are present in most RSGs in the Local Group and that this relation does not depend on the metallicity (Ren et al 2019). In order to consider RSGs "standard candles" (as suggested by Glass 1979), factors like the abundance of irregular variables, mass loss, dust production and the additional sources of long-period variability need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The agreement between the lines and our results is evident. Soraisam et al (2018) found that RSG P-L relation is consistent between the LMC, SMC, Galactic RSGs and the M33 (Yang & Jiang 2011, Yang & Jiang 2012and Soraisam et al 2018, despite the range of metallicities (Ren et al 2019). 0 0.001 0.002 0.003 0.004 0.005 0.006 0.007 0.008 0.009 0.01…”
Section: Red Supergiants In the Lmcmentioning
confidence: 91%
“…The regions of each type of evolved massive star are outlined by the dashed lines with color and magnitude criteria listed in Table 4. Due to the relatively large MLR during the RSG phase, the star could be heavily obscured by the surrounding dust envelope (Smith et al 2001;Massey et al 2005;Levesque et al 2006;Yang et al 2018;Ren et al 2019). Therefore, we also empirically extended the RSG region from the reddest and faintest points of the models to the even redder but not fainter area in order to avoid the contamination from extreme AGBs (x-AGB stars are most likely experiencing a "superwind", where the MLR can increase by a factor of ten, and a thick dust envelope obscures the star at optical wavelengths; van Loon et al 2006;Boyer et al 2011) as shown in the diagrams.…”
Section: Multiwavelength Time-series Datamentioning
confidence: 99%
“…Targets without errors are not shown in the CMDs, while the average photometric uncertainties are indicated when available. Due to the relatively large MLR during the RSGs phase, the star could be heavily obscured by the surrounding dust envelope (Smith et al 2001;Massey et al 2005;Levesque et al 2006;Yang et al 2018;Ren et al 2019). Thus, we also empirically extended the RSGs region from the reddest and faintest points of the models to the even redder but not fainter area, in order to avoid the contamination from extreme AGBs (x-AGBs, stars are most likely to be experiencing a "superwind", where the mass-loss rate can increase by a factor of 10, and a thick dust envelope obscures the star at optical wavelengths; van Loon et al 2006;Boyer et al 2011) as shown in the diagrams.…”
Section: Identifying Evolved Massive Star Candidates On the Color-mag...mentioning
confidence: 99%